2011
DOI: 10.1074/jbc.m111.254599
|View full text |Cite
|
Sign up to set email alerts
|

Prenylated C17orf37 Induces Filopodia Formation to Promote Cell Migration and Metastasis

Abstract: Post-translational modification by covalent attachment of isoprenoid lipids (prenylation) regulates the functions and biological activities of several proteins implicated in the oncogenic transformation and metastatic progression of cancer. The largest group of prenylated proteins contains a CAAX motif at the C-terminal that serves as a substrate for a series of post-translational modifications that convert these otherwise hydrophilic proteins to lipidated proteins, thus facilitating membrane association. C17o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(56 citation statements)
references
References 41 publications
4
52
0
Order By: Relevance
“…Some research has even suggested that actin can be directly phosphorylated by AKT and that the cortical actin remodeling seen during filopodia formation is dependent on AKT-activated proteins [38]. Similarly, prenylated proteins identified for their involvement with filopodia formation in cancer cells have been implicated in migration and participate in the PI3K/AKT pathway [40]. Although we feel that the activity of LMWF5A is not limited to the activation of Akt, evidence suggests that some of the effects of this biologic on BMMSCs can be explained by stimulation of this pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Some research has even suggested that actin can be directly phosphorylated by AKT and that the cortical actin remodeling seen during filopodia formation is dependent on AKT-activated proteins [38]. Similarly, prenylated proteins identified for their involvement with filopodia formation in cancer cells have been implicated in migration and participate in the PI3K/AKT pathway [40]. Although we feel that the activity of LMWF5A is not limited to the activation of Akt, evidence suggests that some of the effects of this biologic on BMMSCs can be explained by stimulation of this pathway.…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16][17]21 However, the role of MIEN1 in the tumor biology of OSCC has not been investigated. Here, we inquired whether MIEN1 is altered in OSCC, thus contributing to tumor progression and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…1C) suggesting possible posttranscriptional and/or post-translational regulation of MIEN1. 16,18 Confocal analysis (Fig. 1D) showed cytoplasmic localization of MIEN1.…”
Section: Mien1 Is Upregulated In Oral Cancer Cell Linesmentioning
confidence: 99%
See 1 more Smart Citation
“…The 'CaaX' group of proteins are known to be farnesylated by the enzyme farnesyltransferase or geranylgeranylated by the enzyme geranylgeranyl transferase type I (GGTase-I) (14). This posttranslational modification of the C-terminal prenylation domain of C35 is essential for its membrane association, which facilitates the induction of filopodia formation (15). Because farnesyl and geranylgeranyl are generated from mevalonate (MVA) which is synthesized by HMG-CoA (16), inhibition of HMGCoA will reduce the production of MVA and in turn decrease the generation of farnesyl and geranylgeranyl, which finally influences the maturation and expression of C35.…”
Section: Resultsmentioning
confidence: 99%